Measuring the investment performance of pension funds: for the purpose of inter-fund comparison - Cohen, Kalman J.; Bank Administration Institute (Park Ridge, Ill.: Bank Administration Institute, 1968)
This report contains the recommendations of the Advisory Committee on measuring the investment performance of pension funds for the purpose of inter-fund comparison. The different parts of the report were primarily the responsibility and work of individuals rather than of the committee as a whole.
Bibliography: p. 222-224.
usc 13/7/17
Loans
Keywords: Pension trusts